HIV Counseling And Testing Services In University Of Uyo Youth Friendly Centre: Impact Of Students’ Knowledge And Perception Of HIV And AIDS - Achalu, Dorathy; Udo, Helen (Advances in Social Sciences Research Journal, 2018)
A study of the impact of HIV Counseling and Testing (HCT) services on students’ knowledge and perception of HIV and AIDS was conducted at the Youth Friendly Centre (YFC), University of Uyo, Uyo, Akwa Ibom State. The purpose was to find out whether the students who received HCT services of the YFC have acquired knowledge on causes, mode of transmission, and prevention of HIV and AIDS, as well as gained improved perception about the infection. A sample of 840 students who had received HCT services at the YFC were randomly selected from four faculties housed in the Town and Annex Campuses of UNIUYO using disproportional random sampling technique. The instrument title “Knowledge and Perception of HIV and AIDS Questionnaire (KPKHIVAIDQ)” was used for data collection. The instrument was validated and pre-tested for reliability using test-retest approach. A reliability coefficient of .82 was obtained after analysis. The instrument was administered on 840 respondents and all were completed, returned and used for analysis. Descriptive statistics (frequencies and percentages) were used for data analysis. The results showed that the students are knowledgeable on causes and modes of transmission of HIV and AIDS. They are not adequately knowledgeable on the preventive measures of HIV and AIDS as they still believed that HIV and AIDS could be prevented through prayers. Still, a little less than one-half of them disagreed on sexual abstinence as means of preventing of HIV and AIDS. The students have different perception of HIV and AIDS as some still believed that they can tell that a person has HIV and AIDS by merely looking at the person’s physical appearance. And that there is no need to take HIV and AIDS test if one is not at risk. The YFC of UNIUYO should intensify enlightenment campaigns and education on HIV and AIDS among the students.